Platelet Activity And Some Immunological Findings In Atherosclerosis and Coronary Heart Disease - AI-Assaf, A.I.S (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The   platelet  activity  and  some  immunological  aspects  ofcoronary heart disease CIID were investigated by employing platelet count and serum levels of IgG,IgM and lgA,C3 and C4.Three groups of  patients were investigated : patients with ischemic heart disease IHD,  patients  with      lliD+hypcrtension  and  patients  with IHD+unstable angina.The results revealed  that the mean of platelets (mm')  was  significantly  reduced   in  IHD+unstable  angina  group2.72.L I.l2 compared with conrol b'TOUp 8.13Â±2.72.With respect to the immunological study, the re;;ults revealed that lgG  level  (mg/dl)  was significantly  reduced in  UIDhypertension group   1113.70Â±8.81  and   in  LHD+unstable angina  857.85Â±17.78compared with control group 1279.33Â±22.2S.The same effect was observed on  IgM,in IHOgroup, the mean was 114.47Â±4.40  and  in UID+hypertension group  was  122.1 0Â±5.32 compared  with  control group 177.25Â±4.86.The mean of complement component C3 was significantly increased in IHD+ hypertension group 197.92.%6.56, also in IHD+unstable angina group 150.750Â±1 0.78 compared wih control group I 02.79Â±I0.38.